Environmental aspects of conversion of the WR-25 coal-fired boiler to gas fuel - Marciniak, Jacek (Instal, 2022)
The article presents the method and the environmental effects of the conversion of the WR-25 water-coal boiler to the WR25-M / G boiler, fired with gaseous fuel. The first part of the article describes which boiler elements have been modernized in order to change the fuel supplied. Then, the determination of the characteristics of the main parameters of the modernized boiler is presented. Finally, a comparison of boiler parameters before and after modernization is presented.
Keywords: gas boiler; conversion; pollution reduction